Demographic Characteristics, Knowledge, Attitudes, and Actions of Mothers Related to Nutrition among Stunting Toddlers - Ida Bagus Eka Utama Wija; Wiradi Suryanegara; Louisa Ariantje Langi; Keswari Aji Patriawati (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Stunting is a chronic nutritional problem that affects children’s growth and development. Indonesia still has a high prevalence of stunting, including in urban areas such as Bogor. Maternal characteristics and nutrition-related behaviors are important factors to consider when designing effective interventions. This study aims to describe maternal demographics, nutrition-related knowledge, attitudes, and practices, as well as the incidence of stunting among toddlers in Gunung Batu Village, Bogor City. A quantitative descriptive observational design was applied, involving all mothers of stunted toddlers aged 6-59 months registered at the Gunung Batu Community Health Center in February 2025. A total of 54 respondents were selected using total sampling. Data on maternal knowledge, attitudes, and practices were collected through questionnaires, while stunting data were obtained from health center records. Descriptive analysis was conducted using frequencies and percentages. The average maternal age was 30.7 years. Most mothers had completed senior high school or vocational education (42.59%) and were housewives (72.22%). All toddlers in the study (N = 54) were classified as stunted. Most mothers demonstrated good levels of knowledge and practices related to toddler nutrition (96.3%), and all reported positive attitudes. Despite these favorable maternal characteristics, stunting persisted among all toddlers in this study. These findings suggest that factors beyond maternal nutrition-related behaviors may contribute to stunting and highlight the need for further studies to identify additional determinants and strengthen prevention strategies. Keywords: Stunting, Knowledge, Attitude, Practice, Mother, Toddler, Demography.